Pengetahuan Remaja dalam Pemeliharaan Kesehatan Reproduksi di SMAN 13 Kota Jambi - Nurfitriani, Nurfitriani; Arifarahmi, Arifarahmi; Putri, Vevi Suryenti; Pebrianti, Dwi Kartika (Jurnal Akademika Baiturrahim Jambi, 2024)
Care of the reproductive organs is critical. If the organs are not appropriately maintained, it can cause various kinds of acne that can cause infection. To stop the infection, cleanliness is needed to maintain the genitalia organs according to religious, cultural, and medical guidance, and can also use alternative therapies. The problems students face have yet to maximize their understanding of reproductive health, especially maintaining the reproductive organs of adolescent sons and daughters. The purpose of the study was to know the picture of adolescent knowledge in the maintenance of reproductive organ health. SMAN 13 Jambi City. The research method used a description survey, with a sample of 104 respondents, by filling out a questionnaire using a Google form. The results of the study are known the characteristics of respondents based on the age of the most aged 16 years (49.1%), the most female gender 56 (53.8%), (99.95%) have received information and most (87.94%) respondents are well knowledgeable in the maintenance of reproductive organs. SMAN 13 continues to monitor and educate its students so that they realize and understand how important it is to maintain the health of reproductive organs for their lives in the future to avoid infectious and non-communicable diseases